Developing noise control legislation (silencing the critics) - Lewis, Anita; DeGagne, David (Canadian Acoustics, 2004)
The noise control legislation, which is essential to have effective industrial noise control regulations in place to minimize the impacts on the environment, is developed. As the Noise Control Directive evolves, it continues to serve industry, the public and the EUB as a useful tool to manage environment noise. The involvement of a multi-stakeholder committee in the development of the Directive and a balanced viewpoint that considers both industry and residents is the basis for the effectiveness and acceptance of the Directive as a fair regulatory process. A logical next step in controlling industrial noise is to make it universal throughout the province. This would require meeting the elements by the appropriate authority.